The rise of China in economic cooperation International in the East Asia Region - Ismail Sultansoy (International Journal of Science and Society, 2020)
East Asian economic characteristics that involve the role of the state as well as the development of the industry, has been relatively creates confidence in the market so that the flow of capital, goods, and services began to lead to the region since the late 20th century. The excess of the advance of China as the new political economic power is also growing wider market in Southeast Asia. The emergence of China as the dominant country in the world political economy are not purely derived from the ability of domestic governance, but also factor disclosure strategy in East Asian economies led by the extractive industry transformation towards manufacturing industry. This expansion translates into core industry sectors in East Asia.This article is intended as a preliminary study on the degree of China's industrial sector expansion in East Asia, as well as identifying the internal factors in the expansion of China's influence. By using the approach as well as the extended behavioralism regionalism as a tool of analysis , this article finds that China is a state actor who is more emphasis on manufacturing and trade sectors of consumer goods as a strategy into an economic hegemon in its own region , formerly controlled by Japan